2021
DOI: 10.3390/ijms22094365
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Long Non-Coding RNAs in Systemic Sclerosis Monocytes: A Potential Role for PSMB8-AS1 in Altered Cytokine Secretion

Abstract: Systemic sclerosis (SSc) is a chronic autoimmune disease mainly affecting the connective tissue. In SSc patients, monocytes are increased in circulation, infiltrate affected tissues, and show a pro-inflammatory activation status, including the so-called interferon (IFN) signature. We previously demonstrated that the dysregulation of the IFN response in SSc monocytes is sustained by altered epigenetic factors as well as by upregulation of the long non-coding RNA (lncRNA) NRIR. Considering the enormously diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…LncPSMB8-AS1 is also upregulated in the blood monocytes of patients with early SSc, ncSSc and dsSSc and is implicated in immune cell activation and vesicle-related transport. PSMB8-AS1 knockdown resulted in decreased concentrations of IL-6 and TNFa in the cell-free supernatant (58), which are linked to fibrotic (80,81), and ILD (82,83). Thus, PSMB8-AS1 can modulate monocyte activation in SSc and secretion of proinflammatory cytokines (58).…”
Section: Lncrnamentioning
confidence: 99%
See 1 more Smart Citation
“…LncPSMB8-AS1 is also upregulated in the blood monocytes of patients with early SSc, ncSSc and dsSSc and is implicated in immune cell activation and vesicle-related transport. PSMB8-AS1 knockdown resulted in decreased concentrations of IL-6 and TNFa in the cell-free supernatant (58), which are linked to fibrotic (80,81), and ILD (82,83). Thus, PSMB8-AS1 can modulate monocyte activation in SSc and secretion of proinflammatory cytokines (58).…”
Section: Lncrnamentioning
confidence: 99%
“…PSMB8-AS1 knockdown resulted in decreased concentrations of IL-6 and TNFa in the cell-free supernatant (58), which are linked to fibrotic (80,81), and ILD (82,83). Thus, PSMB8-AS1 can modulate monocyte activation in SSc and secretion of proinflammatory cytokines (58).…”
Section: Lncrnamentioning
confidence: 99%
“… 54 The upregulation of PSMB8‐AS1 can modulate the secretion of IL‐6 and tumour necrosis factor (TNF) α, two pivotal proinflammatory cytokines. 55 It is concluded that lnc‐PSMB8‐AS1 can be used as a novel host factor for developing antiviral therapy against influenza virus infection. 56 …”
Section: Long Noncoding Rnasmentioning
confidence: 99%
“… 95 The differentially expressed ncRNA00201 and PSMB8-AS1 in blood and MGC12916 in fibroblasts were also confirmed to be important players in the pathogenesis of SSc. 40 , 96 , 97 The involvement of lncRNAs in the pathogenesis of scleroderma is intricate and complicated, which may be through the epigenetic regulation of the gene itself, interacting with miRNAs, or affecting the secretion of important cytokines such as IL-6 and TNFα, 97 and participating in regulating the expression of fibrosis-related genes. At present, the field of lncRNA is still in its infancy, and related research is still limited but proved to be effective.…”
Section: Non-coding Rna-mediated Regulationmentioning
confidence: 99%